Carbonic anhydrase inhibitor induces otic hair cell apoptosis via an intrinsic pathway and ER stress in zebrafish larvae. (2021) - Matsumoto, Hiroko; Miyagi, Hisako; Nakamura, Nobuhiro; Shiga, Yasuhiro; Ohta, Toshihiro; Fujiwara, Shoko; Tsuzuki, Mikio
Graphical abstract: Highlights: CA inhibitor EZA causes lateral line organ death in zebrafish larvae. Neuromast hair cells are especially sensitive to EZA during embryo development. EZA induces apoptosis in otic hair cells via an intrinsic pathway and ER stress. Abstract: Carbonic anhydrase (CA) catalyzes reversible hydration of CO2 to HCO3 − to mediate pH and ion homeostasis. Some chemical pollutants have been reported to have inhibitory effects on fish CA. In this study, we investigated effects of a CA inhibitor ethoxyzolamide (EZA) on neuromasts development during zebrafish embryogenesis, since embryogenesis in aquatic organisms can be particularly sensitive to water pollution. EZA caused alteration of pH and calcium concentration and production of reactive oxygen species (ROS) in larvae, and induced apoptosis in hair cells especially in the otic neuromast, in which CA2 was distributed on the body surface. mRNA levels of apoptotic genes and caspase activities were increased by EZA, whereas anti-oxidants and apoptotic inhibitors, Bax, NF-κB, and p53 inhibitors significantly relieved the induction of hair cell death. Also, mRNA levels of Bip and CHOP, which are induced in response to ER stress, were upregulated by EZA, suggesting that EZA induces otic hair cell apoptosis via the intrinsic mitochondrial pathway and ER stress. Our results demonstrated an essential role of CA in neuromast development via maintenance of ion transport and pH, and that the CA, which is directly exposed to the ambient water, shows marked sensitivity to EZA.